Metabolism of polyethylene glycol by two anaerobic bacteria, Desulfovibrio desulfuricans and a Bacteroides sp. - Dwyer, D F (1986)
Two anaerobic bacteria were isolated from polyethylene glycol (PEG)-degrading, methanogenic, enrichment cultures obtained from a municipal sludge digester. One isolate, identified as Desulfovibrio desulfuricans (strain DG2), metabolized oligomers ranging from ethylene glycol (EG) to tetraethylene glycol. The other isolate, identified as a Bacteroides sp. (strain PG1), metabolized diethylene glycol and polymers of PEG up to an average molecular mass of 20,000 g/mol [PEG 20000; HO-(CH2-CH2-O-)nH]. Both strains produced acetaldehyde as an intermediate, with acetate, ethanol, and hydrogen as end products. In coculture with a Methanobacterium sp., the end products were acetate and methane. Polypropylene glycol [HO-(CH2-CH2-CH2-O-)nH] was not metabolized by either bacterium, and methanogenic enrichments could not be obtained on this substrate. Cell extracts of both bacteria dehydrogenated EG, PEGs up to PEG 400 in size, acetaldehyde, and other mono- and dihydroxylated compounds. Extracts of Bacteroides strain PG1 could not dehydrogenate long polymers of PEG (greater than or equal to 1,000 g/mol), but the bacterium grew with PEG 1000 or PEG 20000 as a substrate and therefore possesses a mechanism for PEG depolymerization not present in cell extracts. In contrast, extracts of D. desulfuricans DG2 dehydrogenated long polymers of PEG, but whole cells did not grow with these polymers as substrates. This indicated that the bacterium could not convert PEG to a product suitable for uptake.